Transition metal phosphorus trichalcogenide (MPX3) as saturable absorber for mode-locked thulium-doped fluoride fiber laser / Azim Danial Azam - Azim Danial , Azam (2023)
In this work, the performance of three materials from the transition metal phosphorus trichalcogenide family (MPX3) for generation of mode-locked pulses in the optical S-band region using thulium-doped fluoride fiber (TDFF) as gain medium were investigated. The advancement of technology and rise of industrial revolution 4.0 brings about a bigger need for ultrafast long-range telecommunication. The current use of C-band and L-band optical telecommunications are quickly being saturated. To encounter this, one prospect is to expand into the S-band. As such, major advancements of optical amplification technology for S-band is required. Generation of laser in S-band region was usually achieved by Erbium-doped fiber (EDF) as the gain medium. However, the high phonon loss of silica fiber in S-band reduces its efficiency. The alternative of this is the ZBLAN glass or known as fluoride glass. When doped with Thulium, this gain medium emits at 1500 nm wavelength when pumped with 1400 nm laser source. This is right within the S-band region. Furthermore, the low phonon loss of fluoride glass makes the laser system more efficient. Mode-locked pulse generation in the S-band region can be achieved through active or passive means. Passive pulse generation is comparatively simpler and cheaper than active in order to obtain megahertz repetition rates and picosecond pulse width. Previous studies have used semiconductor-based saturable absorber (SESAM) and carbon-based SA such as graphene. The use of MPX3 material as saturable absorber is interesting as these materials have been proven in semiconductor and energy storage applications. The proposed laser system can shed light on the practicality of a new class of 2D material as a viable optical material in wide variety of photonics applications.